Beautiful, gruesome, and true : artists at work in the face of war - Wilson-Goldie, Kaelen (Columbia Global Reports, 2022)
"Wilson-Goldie memorably profiles three artists who work in widely separated locations, but who share a commitment to conveying the emotional and political truth of some of the worst horrors the world has to offer"--